2009
DOI: 10.1111/j.1365-2230.2008.02902.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute generalized exanthematous pustulosis after pemetrexed, and recurrence after re-introduction

Abstract: Acute generalized exanthematous pustulosis (AGEP) is a rare cutaneous reaction, which in most cases, is related to medication. Pemetrexed is an antifolate drug, approved for treatment of metastatic non-small-cell lung cancer (NSCLC) and malignant pleural mesothelioma (MPM). We present a case of AGEP caused by pemetrexed, and a recurrence of this eruption after re-introduction of pemetrexed despite use of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…24,29) Ishikawa et al reported that the incidence of pemetrexed-induced rash was lower in patients who received supplementary corticosteroids, compared to that in patients who did not receive supplementary corticosteroids, although this difference was not statistically significant (23.5% vs. 36.2%, p=0.17). 24) However, the absence of statistical significance might be related to the relatively low number of patients who were enrolled in that study (n=81). In addition, those authors did not evaluate a cutoff dose or the dosing period.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…24,29) Ishikawa et al reported that the incidence of pemetrexed-induced rash was lower in patients who received supplementary corticosteroids, compared to that in patients who did not receive supplementary corticosteroids, although this difference was not statistically significant (23.5% vs. 36.2%, p=0.17). 24) However, the absence of statistical significance might be related to the relatively low number of patients who were enrolled in that study (n=81). In addition, those authors did not evaluate a cutoff dose or the dosing period.…”
Section: Discussionmentioning
confidence: 98%
“…Pemetrexed is associated with a high incidence of rash, and is occasionally responsible for more severe symptoms, such as acute generalized exanthematous pustulosis 25) and Lyell's syndrome. 26,27) Therefore, it is important to prevent the development of rash and to decrease its severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These manifestations include myelosuppression (anemia, neutropenia and thrombopenia), and various digestive tract dysfunctions such as nausea, vomiting, diarrhea, constipation, anorexia, stomatitis or oral erosions (24). In oncological practice, the dose-limiting toxicity (DLT) of pemetrexed is determined by its myelosuppression although certain other non-haematological toxicities may occur before myelosuppression is reached.…”
Section: Cutaneous Adverse Reactionsmentioning
confidence: 99%
“…In some instances, however, CAR identification was more clearly supported (24)(25)(26)(27)(28)(29)(30)(31)(32). The specific diseases associated with these events were reported to be alopecia (22), acute generalized exanthematous pustulosis (AGEP) (24), urticarial vasculitis (25), radiation recall dermatitis (RRD) (26)(27)(28), toxic epidermal necrolysis (TEN) (29,30), eyelid edema (31) and PL-like dermatitis (32).…”
Section: Cutaneous Adverse Reactionsmentioning
confidence: 99%